2018
DOI: 10.1007/s00259-018-4214-x
|View full text |Cite
|
Sign up to set email alerts
|

18F-labeled anti-human CD20 cys-diabody for same-day immunoPET in a model of aggressive B cell lymphoma in human CD20 transgenic mice

Abstract: Purpose Metabolic imaging using [ 18 F]FDG is the current standard for clinical PET; however, some malignancies (e.g., indolent lymphomas) show low avidity for FDG. The majority of B cell lymphomas express CD20, making it a valuable target both for antibody-based therapy and imaging. We previously developed PET tracers based on the humanised anti-CD20 antibody obinutuzumab (GA101). Preclinical studies showed that the smallest bivalent fragment, the cys-diabody (GAcDb, 54.5 kDa) with a peak uptake at 1-2 h post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…The analysis suggested that sameday imaging would be best accomplished with the diabody format (3-to 5-h interval after injection) and that if the imaging figure of merit was calculated for 18 F, only the diabody was competitive, as the larger-sized fragments have half-lives that are too long and the smaller monovalent scFv showed much shorter tumor retention. The in vivo results using 18 F-DMLsCy5-A2cDb presented in this work indeed show that same-day immuno-PET imaging is feasible and further corroborate previous studies with 18 F-labeled diabodies in several models (human epidermal growth factor receptor 2, carcinoembryonic antigen, CD20) (29)(30)(31).…”
Section: Discussionsupporting
confidence: 89%
“…The analysis suggested that sameday imaging would be best accomplished with the diabody format (3-to 5-h interval after injection) and that if the imaging figure of merit was calculated for 18 F, only the diabody was competitive, as the larger-sized fragments have half-lives that are too long and the smaller monovalent scFv showed much shorter tumor retention. The in vivo results using 18 F-DMLsCy5-A2cDb presented in this work indeed show that same-day immuno-PET imaging is feasible and further corroborate previous studies with 18 F-labeled diabodies in several models (human epidermal growth factor receptor 2, carcinoembryonic antigen, CD20) (29)(30)(31).…”
Section: Discussionsupporting
confidence: 89%
“…In a broad range of scattering angles and concentrations the experimental data showed the expected linear behavior and consequently the Zimm formalism can be applied to these linear regions. In Figure 8 the results with a linear fit and the extrapolation according to the Equations (13) and (14). The intercept of both extrapolated lines with the y-axis is at 2.0666 × 10 −5 mol·g −1 .…”
Section: Zimm Analysismentioning
confidence: 97%
“…Antibodies feature highly specific binding to a wide range of antigens. Therefore, antibodies are being increasingly used for therapeutical purposes, such as passive immunization [5,6], immunomodulation (e.g., as therapy for multiple sclerosis) [7,8], cancer therapy (e.g., Trastuzumab [9][10][11] or monomethyl auristatin E [12]) or for medical imaging (e.g., immunoscintigraphy [13,14]). Besides the use of whole antibodies, the application of antibody fragments is widely spread and provides further advantages [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the comprehension of antibody structure and the development of immunology, molecular biology, diversified antibody fragments (as illustrated in Figure 1) are constructed through antibody engineering. All antibody fragments retain antigen-specific [26]. Meanwhile, current antibody fragment preparation techniques are relatively complete and there are many methods to choose from, such as phage display technology, yeast display technology [27][28][29].…”
Section: Basic Structure and Characteristics Of Antibody Fragmentsmentioning
confidence: 99%